Cost-effective Paper-microfluidics Technology for the Assessment of Diverse Milk Adulterations - Jaiswal, Sonal; Chowdhury, Pradyumn; Kumari, Priyanka; Verma, Deepti; Prabhakar, Amit (Current Analytical Chemistry, 2025)
<span class=
Keywords: Micro-channels